A doped iron-based MOFs nanozyme and its application in detecting ascorbic acid

The doped iron-based MOFs nanoenzyme prepared by hydrothermal reaction enhances conductivity and catalytic activity by introducing cobalt, solving the problem of difficulty in detecting ascorbic acid in the prior art, and achieving efficient and sensitive ascorbic acid detection.

CN119158628BActive Publication Date: 2025-02-14QILU INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411660412.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

It is difficult to prepare a doped iron-based nanoenzyme for efficient detection of ascorbic acid, and the existing nanoenzymes can only detect glucose and cannot meet the detection needs of ascorbic acid.

Method used

Ferrous chloride, cobalt chloride and dimethylimidazole are used as raw materials to prepare doped iron-based MOFs nanoenzymes through hydrothermal reaction, and cobalt is introduced to enhance the conductive properties and catalytic activity of the material.

Benefits of technology

The prepared doped iron-based MOFs nanoenzymes were detected at 0.5671 μM when detecting ascorbic acid, and their catalytic activity was significantly improved, which could maintain activity in a wider pH and temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158628B_ABST
    Figure CN119158628B_ABST
Patent Text Reader

Abstract

The present invention discloses a doped iron-based MOFs nanozyme and its application in detecting ascorbic acid, and relates to the technical field of biomolecule detection. The present invention adopts ferrous chloride, cobalt chloride and dimethylimidazole as raw materials, and obtains a doped iron-based MOFs nanozyme through a hydrothermal reaction. The doped iron-based MOFs nanozyme can construct a colorimetric detection platform for detecting ascorbic acid. The present invention improves the electron transfer efficiency by introducing cobalt to enhance the conductivity of the material, thereby improving the catalytic activity. The combination of iron and cobalt can promote the interaction between metals, and the synergistic effect can reduce the migration and loss of metal ions, thereby improving the catalytic activity and structural stability of the nanozyme. When the doped iron-based MOFs nanozyme prepared by the present invention detects ascorbic acid, its detection limit is 0.5671 μM.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomolecule detection, and in particular to a doped iron-based MOFs nanozyme and an application thereof in detecting ascorbic acid. Background Art

[0002] Ascorbic acid (AA), also known as vitamin C, has strong reducing ability. As an antioxidant and coenzyme factor, it participates in many important biochemical and physiological processes. It can remove active oxygen and some free radicals in the human body, protect cells from oxidative damage and promote immunity, and plays a very important role in maintaining normal life activities of the human body. Lack of ascorbic acid in the human body can lead to sepsis, cardiovascular and cerebrovascular diseases, etc. The human body cannot synthesize ascorbic acid and can only be ingested through food. Therefore, the detection of ascorbic acid content is one of the indicators for analyzing food safety and nutritional components. At the same time, ascorbic acid is widely used in food, medical and cosmetics as a common additive. Therefore, rapid and effective detection of ascorbic acid content is of great practical significance.

[0003] At present, the detection methods of ascorbic acid include: colorimetric analysis, fluorescence analysis and electrochemical analysis, among which colorimetric analysis has attracted much attention due to its simple equipment, low cost, and convenience for on-site analysis and rapid detection. Among the many colorimetric analysis methods, the construction of colorimetric sensors based on nanozymes has become an important colorimetric analysis method. Nanozymes are nanomaterials with enzyme activity characteristics, with structural diversity, simple preparation, low cost and good stability. As a substitute for natural biological enzymes, they have broad application prospects in chemical detection and medical diagnosis.

[0004] In the prior art, "Research on the Nanozyme Properties and Bioanalytical Applications of FeCo-MOF and Its Graphite Composites" (Li Mengyuan, Harbin Institute of Technology, June 2022) discloses FeCo-MOF and its application in detecting glucose. Among them, the preparation method of FeCo-MOF is: FeCl2·6H2O and CoCl2·6H2O solids are mixed with terephthalic acid and dissolved in DMF solution, and FeCo-MOF is obtained by hydrothermal reaction. The prepared FeCo-MOF has intrinsic simulated peroxidase activity and can be used for colorimetric detection of glucose. However, the above-mentioned nanozymes all use terephthalic acid as an organic ligand, and terephthalic acid has a strong planar structure. This structure will cause the MOFs nanozyme to have a larger porosity, and the prepared nanozyme can only detect glucose, while the detection principles of glucose and antioxidant are completely different.

[0005] Therefore, it is necessary to prepare a doped iron-based nanozyme and use it for the detection of ascorbic acid to improve its catalytic activity when used for ascorbic acid detection. Summary of the invention

[0006] In view of the above-mentioned prior art, the purpose of the present invention is to provide a doped iron-based MOFs nanozyme and its application in detecting ascorbic acid. The present invention adopts ferrous chloride, cobalt chloride and dimethylimidazole as raw materials, and obtains a doped iron-based MOFs nanozyme through a hydrothermal reaction. The doped iron-based MOFs nanozyme can construct a colorimetric detection platform for detecting ascorbic acid. The present invention can enhance the conductivity of the material and improve the electron transfer efficiency by introducing cobalt, thereby improving the catalytic activity. The combination of iron and cobalt can promote the interaction between metals, and the synergistic effect can reduce the migration and loss of metal ions, thereby improving the overall structural stability and catalytic activity. When the doped iron-based MOFs nanozyme prepared by the present invention detects ascorbic acid, its detection limit is 0.5671μM.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] In a first aspect of the present invention, a doped iron-based MOFs nanozyme is provided, wherein the doped iron-based MOFs nanozyme is prepared by the following method:

[0009] (1) FeCl2·4H2O and CoCl2·6H2O are mixed, and then added to methanol to mix well to obtain a first mixed solution; the first mixed solution is then added to a dimethylimidazole solution, heated and shaken, and then centrifuged, and the precipitate after centrifugation is collected, and then the precipitate is dispersed in methanol to obtain a precursor solution;

[0010] (2) FeCl2·4H2O and CoCl2·6H2O are mixed, and then added to methanol to mix well to obtain a second mixed solution; the second mixed solution is then mixed with the precursor solution, subjected to a hydrothermal reaction and centrifugation, and the solid after centrifugation is collected, washed, and dried to obtain the doped iron-based MOFs nanozyme.

[0011] Preferably, in step (1), in the first mixed solution, the material-liquid ratio of FeCl2·4H2O, CoCl2·6H2O and methanol is (0.0747-0.4484) g: 0.00447 g: 15 mL.

[0012] Preferably, in step (1), the dimethylimidazole is prepared by mixing dimethylimidazole and methanol at a solid-liquid ratio of (0.6-0.7) g:15 mL.

[0013] Preferably, in step (1), the mass ratio of FeCl2·4H2O in the first mixed solution to dimethylimidazole in the dimethylimidazole solution is (0.0747-0.4484):(0.6-0.7).

[0014] Preferably, in step (1), the heating temperature is 25-35° C. and the shaking time is 12-18 min.

[0015] Preferably, in step (1), the centrifugation time is 8-12 min.

[0016] Preferably, in step (1), the solid-liquid ratio of precipitate to methanol is (0.8-0.9) g:15 mL.

[0017] Preferably, in step (2), in the second mixed solution, the material-liquid ratio of FeCl2·4H2O, CoCl2·6H2O and methanol is (0.0747-0.4484) g: 0.00447 g: 15 mL.

[0018] Preferably, in step (2), the mass ratio of the second mixed solution to the precursor solution is (12.67-12.77): 12.25.

[0019] Preferably, in step (2), the hydrothermal reaction temperature is 60-80° C., and the hydrothermal reaction time is 1 h.

[0020] More preferably, the hydrothermal reaction temperature is 80°C.

[0021] Preferably, in step (2), the centrifugation time is 8-12 min.

[0022] Preferably, in step (2), the drying temperature is 55-65° C. and the drying time is 6 hours.

[0023] The second aspect of the present invention provides the use of the above-mentioned doped iron-based MOFs nanozyme in ascorbic acid detection.

[0024] The third aspect of the present invention provides a method for detecting ascorbic acid using the above-mentioned doped iron-based MOFs nanozyme, comprising the following steps:

[0025] After mixing NaAc-HAc buffer solution, TMB solution, H2O2 solution and doped iron-based MOFs nanozyme solution, a mixed solution is obtained. After the mixed solution is incubated once, its absorbance at 652nm is measured; then, ascorbic acid solutions of different concentrations are mixed with the mixed solution, and the mixture is incubated twice, and the absorbance at 652nm is measured to obtain a linear relationship between the absorbance difference and the ascorbic acid solution, and a standard curve is plotted to obtain a regression equation; the regression equation is then used to detect the ascorbic acid content in the analyte.

[0026] Preferably, the pH of the NaAc-HAc buffer solution is 3.5-4.5, the concentration of the TMB solution is 2.5 mmol / L, the concentration of the H2O2 solution is 0.2 mol / L, and the concentration of the ascorbic acid solution is 10-70 μmol / L.

[0027] Preferably, the doped iron-based MOFs nanozyme solution is made of doped iron-based MOFs nanozyme and deionized water, and the concentration of the doped iron-based MOFs nanozyme solution is 0.1 mg / mL.

[0028] Preferably, the volume ratio of NaAc-HAc buffer solution, TMB-ethanol solution, H2O2 solution, and doped iron-based MOFs nanozyme solution is 8 mL: 2 mL: 10 μL: 200 μL.

[0029] Preferably, the incubation temperature is 45-55° C. and the incubation time is 10 min.

[0030] Preferably, the secondary incubation temperature is 20-25° C., and the primary incubation time is 35-45 s.

[0031] Beneficial effects of the present invention:

[0032] The present invention uses ferrous chloride, cobalt chloride and dimethylimidazole as raw materials, and obtains doped iron-based MOFs nanozymes through hydrothermal reaction. The doped iron-based MOFs nanozymes can construct a colorimetric detection platform for detecting ascorbic acid. The present invention improves the electron transfer efficiency by introducing cobalt to enhance the conductivity of the material. Faster electron transfer can accelerate the catalytic reaction rate and enhance the catalytic activity. The combination of iron and cobalt can promote the interaction between metals, and the synergistic effect can reduce the migration and loss of metal ions, thereby improving the overall structural stability, thereby making the iron-cobalt composite nanozyme have greater operating condition robustness, and can remain active in a wider pH range and temperature range. Therefore, the present invention provides the selection of Co and Fe as metal centers, which have a synergistic effect on improving the catalytic activity of nanozymes. In addition, the detection limit of the doped iron-based MOFs nanozyme prepared by the present invention is 0.5671 μM when detecting ascorbic acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 :Effects of different hydrothermal reaction temperatures on the activity of iron-based MOFs nanozymes;

[0034] Figure 2 :Effects of different doping elements on the activity of doped iron-based MOFs nanozymes;

[0035] Figure 3 :The effect of different doping ratios on the activity of doped iron-based MOFs;

[0036] Figure 4 : XRD diagram of the doped iron-based MOFs nanozyme prepared in Example 2, wherein (a) is its XRD diagram at 5-50°; (b) is its XRD diagram at 10-80°;

[0037] Figure 5 : FT-IR characterization of the doped iron-based MOFs nanozyme prepared in Example 2;

[0038] Figure 6 : SEM image and Mapping image of the doped iron-based MOFs nanozyme prepared in Example 2, wherein (a) is the SEM image of the doped iron-based MOFs nanozyme, (b) is the Mapping image of the Co element, and (c) is the Mapping image of the Fe element;

[0039] Figure 7 : (a) Absorbance graph of the doped iron-based MOFs nanozyme prepared in Example 2 after adding ascorbic acid; (b) Standard curve of the doped iron-based MOFs nanozyme prepared in Example 2 after adding ascorbic acid;

[0040] Figure 8 : Absorbance difference diagram of different substances in Experimental Example 3. DETAILED DESCRIPTION

[0041] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0042] Colorimetric analysis has attracted much attention due to its simple equipment, low cost, and convenience for on-site analysis and rapid detection. Nanozymes are nanomaterials with enzyme activity characteristics, with structural diversity, simple preparation, low cost and good stability. Therefore, the development of a nanozyme-based colorimetric detection of ascorbic acid is of great practical significance. In the prior art, although FeCo-MOF nanozymes are disclosed for colorimetric detection, the detection object is glucose, while the detection object of the present invention is ascorbic acid. As two completely different substances, glucose and ascorbic acid have completely different principles of colorimetric detection.

[0043] Specifically, in the detection of ascorbic acid, TMB is oxidized in the presence of the doped iron-based MOFs nanozyme prepared by the present invention and H2O2 to form blue oxTMB. When ascorbic acid is present, it directly reduces the blue oxTMB to colorless reduced TMB, and the color of the solution gradually becomes lighter. That is, the lighter the blue color of the system, the higher the concentration of ascorbic acid. When detecting glucose, H2O2 is adsorbed onto the surface of the nanozyme and decomposes to generate active oxygen in the form of •OH. At the same time, TMB molecules are adsorbed onto the surface of the active enzyme and react with active oxygen in the form of •OH to oxidize TMB into oxTMB. The color of the solution gradually becomes darker, that is, the darker the blue color of the system, the higher the concentration of glucose.

[0044] Based on this, the present invention provides a doped iron-based MOFs nanozyme and its application in detecting ascorbic acid. Based on the iron-based MOFs nanozyme prepared by FeCl2·4H2O and dimethylimidazole, the present invention explores the effect of doping with different elements on the catalytic activity of the nanozyme, and finally screens out that Co-doped iron-based MOFs nanozyme has the best catalytic activity. After doping with cobalt, the catalytic activity of the nanozyme is improved. The stronger the catalytic ability of the enzyme, the more conducive it is to detecting ascorbic acid.

[0045] Among them, dimethylimidazole (DMMI) has a relatively small structure and good coordination ability. It can form a more complex three-dimensional network structure and can form a stable complex with metal ions. This stability helps to improve the detection sensitivity and accuracy of ascorbic acid. In the detection of ascorbic acid, due to the coordination ability of DMMI, its catalytic performance may be improved due to the active sites it provides, forming a more efficient reaction environment and enhancing the sensing of ascorbic acid. At the same time, DMMI can not only act as a ligand, but also form catalytic active sites inside MOF. In addition, compared with other organic ligands, dimethylimidazole has less interference in simulated biological environments, which can reduce the occurrence of false positives or false negatives, thereby improving detection reliability.

[0046] The introduction of cobalt can enhance the conductivity of the material and improve the efficiency of electron transfer. Faster electron transfer can accelerate the catalytic reaction rate and enhance the catalytic activity. The combination of iron and cobalt can promote the interaction between metals. The synergistic effect can reduce the migration and loss of metal ions, thereby improving the overall structural stability. This makes the iron-cobalt composite nanozyme more robust in operating conditions. For example, it can remain active in a wider pH range and temperature range.

[0047] In the present invention, the preparation method of the NaAc-HAc buffer solution is as follows: sodium acetate solution and glacial acetic acid solution are mixed, and the pH value of the mixed solution is adjusted to 2.0-5.0, wherein the sodium acetate solution is prepared by mixing sodium acetate and distilled water at a solid-liquid ratio of 2.72 g:100 mL, and the glacial acetic acid solution is prepared by mixing glacial acetic acid and distilled water at a volume ratio of 3.6:100.

[0048] The H2O2 solution is prepared by mixing 30% hydrogen peroxide and deionized water in a volume ratio of 1:48. The TMB solution is prepared by mixing TMB and anhydrous ethanol in a solid-liquid ratio of 0.03 g:50 mL and then ultrasonically treating for 30 minutes.

[0049] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0050] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0051] Embodiment 1:

[0052] The effects of different hydrothermal temperatures, different doping elements, and different doping ratios on the catalytic activity of the prepared nanozymes were investigated. The absorbance of the detection system was used to reflect the catalytic activity of the nanozymes. The greater the absorbance, the stronger the catalytic activity of the nanozymes.

[0053] The absorbance detection steps are:

[0054] 8 mL of NaAc-HAc buffer solution with a pH of 4.0, 2 mL of 2.5 mmol TMB solution, 10 μL of 0.2 mol / L H2O2 solution and 200 μL of 0.1 mg / L nanozyme solution were mixed, placed at room temperature, and shaken for 10 min to obtain a mixed solution. The mixed solution was transferred to a cuvette and its absorbance at 652 nm was measured using an ultraviolet spectrophotometer (UV-752N).

[0055] 1. Water heating temperature

[0056] The specific steps are:

[0057] (1) Dissolve 0.7474 g of FeCl2·4H2O in 15 mL of methanol to obtain a ferrous chloride solution; then add the ferrous chloride solution to a dimethylimidazole solution, shake in a water bath at 30°C for 15 min, centrifuge for 10 min, collect the precipitate after centrifugation, mix 0.85 g of the precipitate with 15 mL of methanol, and obtain a precursor solution; wherein the dimethylimidazole solution is prepared by mixing 0.616 g of dimethylimidazole and 15 mL of methanol;

[0058] (2) Dissolve 0.7474 g FeCl2·4H2O in 15 mL methanol to obtain a ferrous chloride solution; then slowly pour the ferrous chloride solution into the precursor solution and mix well to obtain a mixed solution. The mixed solution is placed at 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, and 180°C for 1 h, centrifuged for 10 min, and the precipitate after centrifugation is collected and washed and dried to obtain an iron-based MOFs nanozyme.

[0059] (3) The absorbance of the iron-based MOFs nanozymes prepared at different hydrothermal reaction temperatures was detected. Figure 1 shown.

[0060] like Figure 1As shown in the figure, other variables remain unchanged. The catalytic activity of the iron-based MOFs nanozyme shows a trend of first increasing and then decreasing with the gradual increase of the hydrothermal reaction temperature. Among them, when the hydrothermal reaction temperature is 80°C, the activity of the iron-based MOFs nanozyme is the highest. Temperature affects the crystal structure of the nanozyme. When the temperature is low, the iron element is not completely polymerized to form nanospheres, resulting in low enzyme activity. When the temperature is too high, the MOFs material will agglomerate, the active sites will be covered, and the enzyme activity will decrease.

[0061] 2. Doping elements

[0062] The specific steps are:

[0063] (1) Weigh 0.3737 g of FeCl2·4H2O, mix FeCl2·4H2O with chloride salts corresponding to different doping elements, and add 15 mL of methanol to obtain a mixed solution, wherein the amount of chloride salts of different doping elements added is shown in Table 1;

[0064] (2) adding the mixed solution in step (1) to the dimethylimidazole solution, shaking in a water bath at 30°C for 15 minutes, centrifuging for 10 minutes, collecting the precipitate after centrifugation, and mixing the precipitate with 15 mL of methanol to obtain a precursor solution;

[0065] Wherein, the dimethylimidazole solution is prepared by mixing 0.616 g of dimethylimidazole and 15 mL of methanol;

[0066] (3) slowly pouring the mixed solution in step (1) into the above-mentioned precursor solution, mixing evenly, placing it at 80°C for hydrothermal reaction for 1 hour, centrifuging it for 10 minutes, collecting the precipitate after centrifugation, washing and drying it, and obtaining the doped iron MOFs nanozyme;

[0067] (4) The absorbance of the iron-doped MOFs nanozymes prepared after doping with different elements was detected respectively. The results are as follows: Figure 2 shown.

[0068] Table 1 Chloride salts corresponding to different doping elements and their addition amounts

[0069]

[0070] Depend on Figure 2 It can be seen that, except for the increase in absorbance of the nanozymes obtained after Co and Ni doping, the absorbance of the nanozymes obtained after doping with other doping elements did not increase. At the same time, in comparison, the absorbance of the nanozymes obtained after Co doping was higher, and correspondingly, the catalytic activity of the nanozymes obtained after Co doping was better. This is because Co and Fe have similar pyrite structures, and Co ions are easier to dope into Fe.

[0071] 3. Doping ratio

[0072] The specific steps are:

[0073] (1) After mixing 0.3737 g of FeCl2·4H2O with different masses of CoCl2·6H2O, 15 mL of methanol was added to obtain mixed solutions, wherein the molar ratios of FeCl2·4H2O and CoCl2·6H2O were 120:1, 100:1, 80:1, 60:1, 40:1 and 20:1, respectively;

[0074] (2) adding the mixed solution in step (1) to the dimethylimidazole solution, shaking in a water bath at 30°C for 15 minutes, centrifuging for 10 minutes, collecting the precipitate after centrifugation, and mixing the precipitate with 15 mL of methanol to obtain a precursor solution; wherein the dimethylimidazole solution is prepared by mixing 0.616 g of dimethylimidazole and 15 mL of methanol;

[0075] (3) slowly pouring the mixed solution in step (1) into the above-mentioned precursor solution, mixing evenly, placing it at 80°C for hydrothermal reaction for 1 hour, centrifuging it for 10 minutes, collecting the precipitate after centrifugation, washing and drying it, and obtaining the doped iron MOFs nanozyme;

[0076] (4) The absorbance of the doped iron MOFs nanozymes prepared with different doping ratios was detected. Figure 3 shown.

[0077] Depend on Figure 3 It can be seen that when the doping ratio of Fe and Co is 100:1, the synthesized nanozyme has the best catalytic activity while keeping other variables unchanged. First of all, this is because the atomic radius of Fe ions is similar to that of Co ions, which plays a key role in nanozymes. An appropriate amount of Fe content can ensure the number and activity of catalytic centers, thereby achieving efficient catalytic performance. When the Fe content is too high, it may cause the interaction between the catalytic centers to be too strong, which is not conducive to the catalytic reaction.

[0078] Example 2: Preparation method of Co-doped iron-type MOFs nanozyme

[0079] (1) 0.3737 g of FeCl2·4H2O and 0.00447 g of CoCl2·6H2O were mixed, and then added to 15 mL of methanol to obtain a first mixed solution; the first mixed solution was then added to a dimethylimidazole solution, heated and shaken at 30°C for 15 min, and then centrifuged for 10 min. The precipitate after centrifugation was collected, and 0.85 g of the precipitate was dispersed in 15 mL of methanol to obtain a precursor solution;

[0080] The dimethylimidazole solution is prepared by mixing 0.616 g of dimethylimidazole and 15 mL of methanol, and the mass ratio of FeC12·4H2O in the mixed solution to dimethylimidazole in the dimethylimidazole solution is 0.3737 g:0.616 g;

[0081] (2) After mixing 0.3737 g of FeCl2·4H2O and 0.00447 g of CoCl2·6H2O, add them into 15 mL of methanol and mix well to obtain a second mixed solution; then, 12.25 g of the second mixed solution and 12.72 g of the precursor solution were mixed, hydrothermally reacted at 80 °C for 1 h, and centrifuged for 10 min. The solid after centrifugation was collected, washed, and dried at 60 °C for 6 h to obtain the doped iron-based MOFs nanozyme.

[0082] Example 3: Preparation method of Co-doped iron-type MOFs nanozyme

[0083] (1) After mixing 0.0747 g FeCl2·4H2O and 0.00447 g CoCl2·6H2O, add them to 15 mL methanol and mix well to obtain a first mixed solution; then add the first mixed solution to a dimethylimidazole solution, heat and shake at 25°C for 12 min, and then centrifuge for 8-12 min. Collect the precipitate after centrifugation, and then disperse 0.8 g of the precipitate in 15 mL methanol to obtain a precursor solution;

[0084] The dimethylimidazole solution is prepared by mixing 0.6 g of dimethylimidazole and 15 mL of methanol, and the mass ratio of FeC12·4H2O in the mixed solution to dimethylimidazole in the dimethylimidazole solution is 0.0747:0.6;

[0085] (2) After mixing 0.0747 g of FeCl2·4H2O and 0.00447 g of CoCl2·6H2O, add them into 15 mL of methanol and mix well to obtain a second mixed solution; then, 12.25 g of the second mixed solution and 12.67 g of the precursor solution were mixed, hydrothermally reacted at 60 °C for 1 h, and centrifuged for 8 min. The solids after centrifugation were collected, washed, and dried at 55 °C for 6 h to obtain doped iron-based MOFs nanozyme.

[0086] Example 4: Preparation method of Co-doped iron-type MOFs nanozyme

[0087] (1) 0.4484 g of FeCl2·4H2O and 0.00447 g of CoCl2·6H2O were mixed, and then added to 15 mL of methanol to obtain a first mixed solution; the first mixed solution was then added to a dimethylimidazole solution, heated and shaken at 35°C for 18 min, and then centrifuged for 12 min. The precipitate after centrifugation was collected, and 0.9 g of the precipitate was dispersed in 15 mL of methanol to obtain a precursor solution;

[0088] The dimethylimidazole solution is prepared by mixing 0.7 g of dimethylimidazole and 15 mL of methanol, and the mass ratio of FeC12·4H2O in the mixed solution to dimethylimidazole in the dimethylimidazole solution is 0.4484:0.7;

[0089] (3) After mixing 0.4484 g of FeCl2·4H2O and 0.00447 g of CoCl2·6H2O, add them into 15 mL of methanol and mix well to obtain a second mixed solution; then, 12.25 g of the second mixed solution and 12.77 g of the precursor solution were mixed, hydrothermally reacted at 70 °C for 1 h, centrifuged for 12 min, and the solids after centrifugation were collected, washed, and dried at 65 °C for 6 h to obtain the doped iron-based MOFs nanozyme.

[0090] Embodiment 5:

[0091] The doped iron-based MOFs nanozyme prepared in Example 2 was used for colorimetric detection of ascorbic acid to explore the effects of different pH values ​​of NaAc-HAc buffer solutions and different incubation temperatures on the catalytic activity of the nanozyme. The absorbance of the nanozyme system under different conditions was detected to reflect the catalytic activity of the nanozyme. The absorbance detection method was the same as in Example 1.

[0092] The specific steps for colorimetric detection of ascorbic acid are:

[0093] 8 mL of NaAc-HAc buffer solution with a pH of 4.0, 2 mL of 2.5 mmol TMB solution, 10 μL of 0.2 mol / L H2O2 solution and 200 μL of 0.1 mg / L nanozyme solution were mixed, incubated and shaken at room temperature for 10 min to obtain a mixed solution, which was transferred to a cuvette and its absorbance at 652 nm was measured using an ultraviolet spectrophotometer (UV-752N).

[0094] 1. pH of NaAc-HAc buffer solution

[0095] In this experiment, the pH of the NaAc-HAc buffer solution was adjusted to 2.0, 2.5, 3.0, 3.5, 4.0, 4.5 and 5.0, respectively, and the absorbance of the nanozymes prepared at different pH values ​​of the NaAc-HAc buffer solution was investigated. The results are shown in Table 2.

[0096] Table 2 Absorbance of doped iron-based MOFs nanozymes at different pH values ​​of HAc-NaAc buffer solutions

[0097]

[0098] As can be seen from Table 2, when pH = 3.5, the activity of the doped iron-based MOFs nanozyme is the best. This is because the active center of the enzyme has a higher affinity in this environment. By promoting the close binding of the substrate and the nanozyme, the activity of the nanozyme is significantly improved. When the pH is close to 5, the activity of the enzyme suddenly decreases significantly. This is because there is a certain amount of H in the solution. + TMB must first react with H + The hydride is generated and then catalyzed by the enzyme. However, under this pH condition, TMB hardly reacts with H + The formation of hydrides leads to a decrease in enzyme activity.

[0099] 2. Incubation temperature

[0100] In this experiment, the incubation temperatures were adjusted to 30°C, 40°C, 50°C, 60°C, 70°C and 80°C during the colorimetric detection of ascorbic acid, and the absorbance of the nanozymes prepared at different incubation temperatures was investigated. The results are shown in Table 3.

[0101] Table 3 Absorbance of doped iron-based MOFs nanozymes at different incubation temperatures

[0102]

[0103] As can be seen from Table 3, the activity of the doped iron-based MOFs nanozyme is the highest at 50°C. This is because the molecular vibration of the enzyme is inactive at low temperatures and the activity is not high. As the temperature gradually increases, the molecular activity of the enzyme is also gradually enhanced, and the peroxidase and TMB will react faster. The faster the reaction, the faster the rate, and the higher the activity. However, when the temperature rises to 60°C, the activity begins to gradually weaken. This is because the high temperature causes TMB to be oxidized into a yellow product, diimide salt, and the absorption peak at 652nm slowly decreases. At the same time, the non-covalent interaction force inside the enzyme is destroyed, resulting in structural damage, affecting the adsorption of active substances, and thus the enzyme activity decreases.

[0104] In summary, when doped iron-based MOFs nanozymes are used for colorimetric detection of ascorbic acid, the optimal pH of the HAc-NaAc buffer solution used is 3.5 and the incubation temperature is 50°C.

[0105] Example 6: Method for detecting ascorbic acid using doped iron-based MOFs nanozymes

[0106] 8 mL of NaAc-HAc buffer solution with a pH of 3.5, 2 mL of 2.5 mmol / L TMB solution, 10 μL of 0.2 mol / L H2O2 solution and 200 μL of 0.1 mg / mL doped iron-based MOFs nanozyme solution were mixed to obtain a mixed solution. The mixed solution was incubated at 50°C for 10 min, and its absorbance at 652 nm was measured. Then, ascorbic acid solutions of different concentrations (10 μmol / L, 15 μmol / L, 20 μmol / L, 25 μmol / L, 30 μmol / L, 35 μmol / L, 40 μmol / L, 50 μmol / L, 60 μmol / L, 70 μmol / L) were mixed with the mixed solution, incubated at 25°C for 40 s, and the absorbance at 652 nm was measured to obtain a linear relationship between the absorbance difference (ΔA) and the ascorbic acid solution. A standard curve was drawn. The results are shown in FIG. Figure 7 As shown, a regression equation is obtained; and the regression equation is then used to detect the ascorbic acid content in the test object, wherein the difference in absorbance is obtained by subtracting the absorbance after the second incubation from the absorbance after the first incubation.

[0107] The doped iron-based MOFs nanozyme solution is made of doped iron-based MOFs nanozyme and deionized water. The volume ratio of the ascorbic acid solution to the doped iron-based MOFs nanozyme solution in the mixed solution is 1500:200.

[0108] Depend on Figure 7 It can be seen that the standard curve is ΔA=0.01596+0.00529×[AA]; where ΔA is the absorbance difference and [AA] is the concentration of ascorbic acid in μmol / L. The intercept is 0.01596±0.00154 and the slope is 0.00529±5.70535×10 -5 , the residual sum of squares is 1.13920×10 -5 , R 2 is 0.99942, and the adjusted R 2 The detection limit was calculated to be 0.5671 μM.

[0109] Comparative Example 1: Preparation of Iron-based MOFs Nanozymes

[0110] (1) Add 0.3737 g FeCl2·4H2O to 15 mL methanol and mix well to obtain ferrous chloride solution;

[0111] (2) Add the ferrous chloride solution to the dimethylimidazole solution, heat and shake at 30°C for 15 minutes, centrifuge for 10 minutes, collect the precipitate after centrifugation, disperse 0.85 g of the precipitate in 15 mL of methanol and mix well to obtain a precursor solution;

[0112] The dimethylimidazole solution is prepared by mixing 0.616 g of dimethylimidazole and 15 mL of methanol; the mass ratio of FeCl2·4H2O in the mixed solution to dimethylimidazole in the dimethylimidazole solution is 0.3737:0.616;

[0113] (3) After mixing 12.25 g of ferrous chloride solution and 12.72 g of precursor solution, the mixture was subjected to hydrothermal reaction at 80 °C for 1 h and then centrifuged for 10 min. The solid after centrifugation was collected, washed, and dried at 60 °C for 6 h to obtain iron-based MOFs nanozyme.

[0114] Comparative Example 2: Preparation of cobalt-based MOFs nanozymes,

[0115] (1) After mixing 0.00447 g of CoCl2·6H2O, add 15 mL of methanol and mix well to obtain a cobalt chloride solution;

[0116] (2) Add the cobalt chloride solution to the dimethylimidazole solution, heat and shake at 30°C for 15 minutes, centrifuge for 10 minutes, collect the precipitate after centrifugation, mix 0.85 g of the precipitate with 15 mL of methanol, and obtain a precursor solution;

[0117] The dimethylimidazole solution is prepared by mixing 0.616 g of dimethylimidazole with 15 mL of methanol; the mass ratio of CoCl2·6H2O in the mixed solution to dimethylimidazole in the dimethylimidazole solution is 0.00447:0.616;

[0118] (3) After mixing 12.25 g of cobalt chloride solution and 12.72 g of precursor solution, the mixture was subjected to hydrothermal reaction at 80 °C for 1 h and then centrifuged for 10 min. The solid after centrifugation was collected, washed, and dried at 60 °C for 6 h to obtain cobalt-based MOF nanozyme.

[0119] Test Example 1:

[0120] The structure of the doped iron-based MOFs nanozyme prepared in Example 2 was characterized. Figure 4-Figure 6 shown.

[0121] The prepared iron-doped MOFs nanozyme was characterized by XRD. Figure 4 As shown. Figure 4 It can be seen that the prepared doped iron-based MOFs nanozyme is a ZIF structure and is composed of iron and cobalt elements. Figure 4 (a) It can be seen that within the scanning range of 5-50°, the diffraction peaks of the synthesized material are consistent with those of the standard spectrum of ZIF-67, proving that its crystal phase is relatively pure and is indeed ZIF-67. Figure 4(b) It can be seen that within the scanning range of 10-80°, the XRD spectrum of the doped iron-based MOFs nanozyme does not show obvious crystal peaks, indicating that the doped iron-based MOFs nanozyme has basically no crystallinity, but at the same time there is a small amount of crystal morphology in the sample, such as the weak crystal peaks between 35.16° and 63.21° that can be seen in the figure. From the above analysis results, it can be seen that the prepared doped iron-based MOFs nanozyme is a MOFs material.

[0122] FT-IR analysis of doped iron-based MOFs nanozymes showed Figure 5 As shown. Figure 5 It can be seen that the doped iron-based MOFs nanozymes are mainly at 440 cm -1 、629 cm -1 , 1040 cm -1 、1620 cm -1 、2830 cm -1 、3370 cm -1 There is a characteristic peak at 440 cm -1 The vibration of the metal coordination bond is caused by the vibration of the metal coordination bond at 629 cm -1 The vibration of the metal-oxygen bond at 1040 cm -1 This peak is due to the vibration of the CO bond and is at 1620 cm -1 This peak is due to the vibration of the C=C bond at 2830 cm -1 This peak is caused by the vibration of the CH bond at 3370 cm -1 This peak is due to the vibration of OH bonds.

[0123] SEM analysis of doped iron-based MOFs nanozymes showed Figure 6 As shown. Figure 6 (a) It can be seen that the prepared doped iron-based MOFs nanozymes present an irregular morphology, including both spherical particles and angular flake microstructures. Figure 6 (b)- Figure 6 (c) It can be seen that Fe and Co elements are evenly distributed in the sample, proving that Co and Fe elements coexist in doped iron-based MOFs nanozymes.

[0124] Test Example 2:

[0125] The catalytic activity of the nanozymes prepared in Example 2 and Comparative Examples 1-2 was tested, and the results are shown in Table 4, wherein the catalytic activity is reflected by testing the absorbance of each nanozyme.

[0126] Specifically, during the absorbance detection process, H2O2 will react with TMB to generate oxTMB, and this color change reaction occurs under the catalysis of the nanozyme. If the activity of the nanozyme is higher and the catalytic ability is stronger, the reaction rate will be faster and more oxTMB will be generated. oxTMB has an absorption peak at 652nm. According to the Lambert-Beer law, the higher the concentration of oxTMB, the greater the absorbance of the system at 652nm. Therefore, by monitoring the absorbance of the TMB color change reaction, the activity of peroxidase can be effectively studied and evaluated. The higher the absorbance, the higher the catalytic activity of the nanozyme.

[0127] The absorbance detection method is as follows: 8 mL of NaAc-HAc buffer solution with a pH of 3.5, 2 mL of 2.5 mmol TMB solution, 10 μL of 0.2 mol / L H2O2 solution and 200 μL of 0.1 mg / L nanozyme solution are mixed, incubated and shaken at 50°C for 10 min to obtain a mixed solution, the mixed solution is transferred to a cuvette, and its absorbance at 652 nm is measured using an ultraviolet spectrophotometer (UV-752N).

[0128] Table 4 Absorbance corresponding to different nanozymes

[0129]

[0130] It can be seen from Table 4 that the absorbance of the iron-based MOFs nanozyme prepared in Comparative Example 1 is 0.266, the absorbance of the cobalt-based MOFs nanozyme prepared in Comparative Example 2 is 0.80, and the absorbance of the cobalt-doped iron-based MOFs nanozyme prepared in the present invention is 0.080. It can be seen that the present invention uses a combination of cobalt and iron as the metal center of the nanozyme, which has a synergistic effect in improving the catalytic activity of the nanozyme.

[0131] Test Example 3: Specificity Detection

[0132] In order to further determine the anti-interference ability of the cobalt-doped iron-based MOFs nanozyme prepared in Example 2 of the present invention when applied to ascorbic acid detection, common interfering substances were also detected, including: glucose, maltose, sucrose, uric acid, sodium chloride, L-proline, L-glutamic acid, L-tryptophan, L-lysine, citric acid, glycine, and the results are as follows: Figure 8 shown.

[0133] The specific detection method is:

[0134] 8 mL of NaAc-HAc buffer solution with a pH of 3.5, 2 mL of 2.5 mmol / L TMB solution, 10 μL of 0.2 mol / L H2O2 solution, and 200 μL of 0.1 mg / mL doped iron-based MOFs nanozyme solution were mixed to obtain a mixed solution, which was incubated at 50°C for 10 min, and its absorbance at 652 nm was measured;

[0135] Then, 40 μM of glucose, maltose, sucrose, uric acid, sodium chloride, L-proline, L-glutamic acid, L-tryptophan, L-lysine, citric acid, glycine and ascorbic acid were mixed with the mixture, incubated at 25°C for 40 seconds, and the absorbance at 652 nm was measured to obtain the absorbance difference (ΔA). The results are shown in FIG. Figure 8 shown.

[0136] Depend on Figure 8 It can be seen that compared with interfering substances such as glucose, the doped iron-based MOFs nanozyme prepared in the present invention has a higher detection selectivity for ascorbic acid and does not need to mask other interfering substances.

[0137] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. Application of a doped iron-based MOFs nanozyme in ascorbic acid detection, characterized in that: The doped iron-based MOFs nanozyme is prepared by the following method: (1) FeCl2·4H2O and CoCl2·6H2O are mixed, and then added to methanol to mix well to obtain a first mixed solution; the first mixed solution is then added to a dimethylimidazole solution, heated and shaken, and then centrifuged, and the precipitate after centrifugation is collected, and the precipitate is dispersed in methanol to obtain a precursor solution; The first mixed solution has a solid-liquid ratio of FeCl2·4H2O, CoCl2·6H2O and methanol of (0.0747-0.4484) g: 0.00447 g: 15 mL; the dimethylimidazole is prepared by mixing dimethylimidazole and methanol at a solid-liquid ratio of (0.6-0.7) g: 15 mL; the mass ratio of FeCl2·4H2O in the first mixed solution and dimethylimidazole in the dimethylimidazole solution is (0.0747-0.4484): (0.6-0.7); the solid-liquid ratio of precipitate and methanol is (0.8-0.9) g: 15 mL; the heating temperature is 25-35° C., and the shaking time is 12-18 min; (2) FeCl2·4H2O and CoCl2·6H2O are mixed, and then added to methanol to mix well to obtain a second mixed solution; the second mixed solution is then mixed with the precursor solution, subjected to a hydrothermal reaction, and centrifuged; the solid after centrifugation is collected, washed, and dried to obtain a doped iron-based MOFs nanozyme; Among them, in the second mixed liquid, the material-liquid ratio of FeCl2·4H2O, CoCl2·6H2O and methanol is (0.0747-0.4484) g: 0.00447 g: 15 mL, and the mass ratio of the second mixed liquid to the precursor solution is (12.67-12.77): 12.25; the hydrothermal reaction temperature is 60-80°C, and the hydrothermal reaction time is 1 h.

2. The use according to claim 1, characterized in that The specific operation of doped iron-based MOFs nanozymes for detecting ascorbic acid is as follows: After mixing NaAc-HAc buffer solution, TMB solution, H2O2 solution and doped iron-based MOFs nanozyme solution to obtain a mixed solution, the mixed solution is incubated once, and its absorbance at 652nm is measured; then, ascorbic acid solutions of different concentrations are mixed with the mixed solution, and then incubated twice, and the absorbance at 652nm is measured, so as to obtain a linear relationship between the absorbance difference and the ascorbic acid solution, draw a standard curve, and obtain a regression equation; and then use the regression equation to detect the ascorbic acid content in the analyte; The pH of the NaAc-HAc buffer solution is 3.5-4.5, the concentration of the TMB solution is 2.5 mmol / L, the concentration of the H2O2 solution is 0.2 mol / L, the concentration of the ascorbic acid solution is 10-70 μmol / L, and the concentration of the doped iron-based MOFs nanozyme solution is 0.1 mg / mL; the primary incubation temperature is 45-55°C, and the primary incubation time is 10 min; the secondary incubation temperature is 20-25°C, and the secondary incubation time is 35-45 s.

Citation Information

Patent Citations

  • FeNiCo oxygenated chemical nanosheet with adjustable metal proportion as well as preparation method and application thereof

    CN108441880A

  • Ferrocobalt modified ZIF-8 composite material as well as preparation method and application thereof

    CN115337964A

  • Method for detecting antioxidant based on cobalt-based nano-enzyme colorimetric sensing array

    CN118090718A

  • Method to make scalable ultrathin hexagonally faceted metal-organic framework (MOF) and method of using same for detecting explosives and other nitro-aromatic compounds

    US20190152995A1